Efektivitas Pelayanan Izin Mendirikan Bangunan Di Kabupaten Lebak - Ailia Lailatul Qodariah; Delly Maulana; Rachmi Yulianti (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2020)
This article discusses about effectiveness of service on DPMPTSP of the Lebak district as well as barriers and solutions in implementing services. In practice, public considers the procedure of IMB’s licensing are hard to understand and complicated so that public and business actors have not processed building permits. The method used in this research is descriptive qualitative method, this research uses data collection methods in the form of observation, interviews and documentation. The result showed that the performance of DPMPTSP’s employees are quite good. This can be seen from the increase in the number of people applying for IMB’s licensing because public trust in the government, especially on DPMPTSP of the Lebak district who has served them well. However, there are some people and business actors who also have minimal information regarding IMB’s licensing so that this becomes tasks for local governments to increase development and local revenue through permissions available on DPMPTSP of the Lebak district.